Strategi Penyelenggaraan Kesejahteraan Sosial Masyarakat Kota Semarang - Charis Charis (Serat Acitya, 2013)
Social welfare issues in the city of Semarang categorized into 7 (Seven) strategic issues, namely i). the poor, (ii). Neglected elderly, (iii). With disabilities, (iv). Abandoned children, (v). street children, (vi). Displaced children under five, (vii). Vagrants and beggars or homeless. The seventh issue of the number of people with social problems in the city of Semarang as many as 45 183 people. This includes a large number compared to the population of the city of Semarang as much as 29,769,676 inhabitants. Steps to be taken by the local government is socialization, coordination of program activities aimed at handling problems Sosisl Welfare to work unit, corresponding duties and functions expressly and openly by promoting synergy in the activities. Private institutions with government and communities to help deal with the problem by organizing asylums or places for them to practice skills on job creation so that they can live independently.